2012
DOI: 10.1016/j.joms.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Salivary Biosensor for Objective Assessment of Surgery-Related Stress

Abstract: PURPOSE To evaluate the clinical utility of a salivary alpha-amylase (sAA) biosensor for assessing oral surgery-related stress responses and the differential effect of the personality trait of pain catastrophizing. PATIENTS AND METHODS We conducted a prospective, cohort study of 76 healthy subjects who underwent elective removal of their third molars. Along with subjects’ self-reports of anxiety and pain, biosensor-facilitated measurements of sAA levels were obtained at multiple time points during the preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…It has been used in a number of studies to provide close to real-time measurement of salivary amylase levels as a biomarker for stress from academic examination (18), a trier social stress test (23), a flight task (24), a simulated space mission (25), and surgeries (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in a number of studies to provide close to real-time measurement of salivary amylase levels as a biomarker for stress from academic examination (18), a trier social stress test (23), a flight task (24), a simulated space mission (25), and surgeries (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The most important putative biomarkers already described in saliva related to pain are cortisol [10], salivary alpha-amylase (sAA) [11], secretory immunoglobulin A (sIgA) [12], testosterone [13], and soluble tumor necrosis factor-α receptor II (sTNFαRII) [14]. Since 1987, cortisol has been by far the most often used biomarker for acute pain [15].…”
Section: Introductionmentioning
confidence: 99%
“…sAA is one [11] even though it undergoes a diurnal variation [2527], and there are several factors that might influence the daily cycle, it still could be helpful for pain assessment [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Those patients had a significant and progressive increase of sAA concentration during orthodontic treatment, but this increase was likewise not linearly correlated with pain intensity. Robles et al 25 found that sAA levels were lower prior to extraction than compared to consult and followup visits. Robles et al 25 hypothesized that both the anticipation of extraction and the effort expended to arrive at the clinic (ie, rushing to be on time) could have led to an increase in autonomic activity.…”
mentioning
confidence: 97%
“…Robles et al 25 found that sAA levels were lower prior to extraction than compared to consult and followup visits. Robles et al 25 hypothesized that both the anticipation of extraction and the effort expended to arrive at the clinic (ie, rushing to be on time) could have led to an increase in autonomic activity. It was thought that this increase would then decrease over time as the patients arrived at the clinic and were able to acclimate to the setting.…”
mentioning
confidence: 97%